2019
DOI: 10.1039/c9gc03179k
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free synthesis of biodiesel precursors from biomass-based furfuryl alcohols in the presence of H2O and air

Abstract: Dimerization of biomass-based furfuryl alcohols to biodiesel precursors was realized by using only H2O and air without adding any other catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…As shown, it could be found that NaHSO 4 and H 2 SO 4 offered higher hydrogen ion concentration in the presence of acetonitrile (MeCN) as the solvent. Besides, Qin et al 24 reported that the oxygen or air atmosphere could significantly affect the outcome of the reaction from 5-MFA to the 5-methylfurancarboxylic acid (MFCA). However, there was no change in the reaction result of this work after we purged the air of the reactor by N 2 (Table 1, entry 12).…”
Section: Experiments and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown, it could be found that NaHSO 4 and H 2 SO 4 offered higher hydrogen ion concentration in the presence of acetonitrile (MeCN) as the solvent. Besides, Qin et al 24 reported that the oxygen or air atmosphere could significantly affect the outcome of the reaction from 5-MFA to the 5-methylfurancarboxylic acid (MFCA). However, there was no change in the reaction result of this work after we purged the air of the reactor by N 2 (Table 1, entry 12).…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Another profitable way of utilizing biomass is converting it to energy products such as alcohol and biodiesel. , Many studies on biofuel have been published in the past 2 decades. Furan derivatives can be converted to biofuels via a further hydrodeoxygenation process because of the relatively higher carbon content, which provides light fractions of C5–C6 bio-gasoline . However, the synthesis methods of urgently demanded jet fuel with long carbon chain alkanes (C7–C15) require the carbon chain elongation of furan derivatives. , According to the literature, there were mainly four methods for elongating the carbon chains of furan derivatives, which include the aldol condensation, hydroxyalkylation/alkylation, polymerization, and C–C coupling.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations